2018
DOI: 10.4102/sajpsychiatry.v24i0.1142
|View full text |Cite
|
Sign up to set email alerts
|

Forensic psychiatric assessment process and outcome in state patients in KwaZulu-Natal, South Africa

Abstract: BackgroundIndividuals who were charged with a serious offence may be referred by courts for forensic psychiatric assessment. The court may declare them as state patients if they are found unfit to stand trial or not criminally responsible because of mental illness or defect.In forensic psychiatry practice, there may be challenges in the forensic psychiatric observation process, and discrepancies may occur between the clinician report and the court’s decision.ObjectivesTo describe elements of the forensic psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
(22 reference statements)
2
8
0
3
Order By: Relevance
“…5,7,19,21,22,23 The finding that there is an association between employment status and fitness to stand trial corresponds with the findings of another South African study. 24 In a study that examined characteristics of IPH perpetrators, mental illness was rarely diagnosed before the incident, 17 contrary to a Dutch study which showed that 59% of offenders had previous contact with psychiatric services. 23 Our study showed that 20% of the sample had been diagnosed with a mental illness prior to the offence.…”
Section: Discussionmentioning
confidence: 95%
“…5,7,19,21,22,23 The finding that there is an association between employment status and fitness to stand trial corresponds with the findings of another South African study. 24 In a study that examined characteristics of IPH perpetrators, mental illness was rarely diagnosed before the incident, 17 contrary to a Dutch study which showed that 59% of offenders had previous contact with psychiatric services. 23 Our study showed that 20% of the sample had been diagnosed with a mental illness prior to the offence.…”
Section: Discussionmentioning
confidence: 95%
“…El presente estudio es el primero en el Perú que cuantifica a las personas inimputables por trastornos mentales que pasaron por el sistema penitenciario a nivel nacional, y describe sus características epidemio- Los resultados sociodemográficos obtenidos permitieron identificar un perfil característico de los pacientes inimputables en la muestra estudiada: de sexo masculino, mediana edad, procedente de la capital o de la sierra, con diferentes años de secundaria concluidos, desempleado o con trabajos sin formación académica especializada, sin pareja e hijos. Este perfil concuerda con otros estudios peruanos 16,17,24 , latinoamericanos 6,25 , europeos 26,27 y africanos 28 . Por otro lado, el estudio realizado en los Estados Unidos encontró una edad media de 42,2 años, mayor que en el presente estudio, aunque solamente se consideraron los inimputables por delitos sexuales.…”
Section: Discussionunclassified
“…Violent crimes are the usual reason for admission to forensic psychiatric units; however, one South African study found that there were cases of individuals being declared state patients even when they did not commit serious crimes. 16 Notably from a South African perspective, there have been two studies from two academic centres that have looked at the profiles of state patients in a specific time frame. 17 , 18 These two studies, however, did not investigate trends in their state patient profiles over a specific time.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the 10-year period of the study, the demographic profiles of the state patients were generally in line with that found in local and international literature where the majority were male, single and unemployed. 16 , 17 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%